Impact of TBTs on trade in ICT goods: Differentiating by regulatory objectives - Mahdi Ghodsi (Central European Economic Journal (CEEJ), 2024)
This paper analyses how different types of technical barriers to trade (TBTs) imposed on imports of information and communications technology (ICT) goods globally affected the value and volume of imported goods during the period of 1996-2018. Key words cited in the TBTs give an indication of the aims behind the imposition of TBTs. The results indicate that TBTs have a strong positive impact on the value of imports. While many key words cited in TBTs notified to the World Trade Organization (WTO) affect the value and volume of imports in a positive way, certain other TBTs function as trade barriers.
Keywords: F13; F14; L15; 330; Information and communications technology; non-tariff measures; technical barriers to trade; World TradeOrganization; Pseudo Poisson Maximum Likelihood